Respons Siswa Terhadap Program Sekolah Binaan SMK Se-Riau Program Kimia Fakultas MIPA Dan Kesehatan UMRI - Nasution, Hasmalina; Siregar, Sri Hilma; Rahayu, Anggi Putri; Syahri, Jufrizal; Prasetya, Prasetya; Hilma, Rahmiwati; Syafri, Rahmadini; Sari, Meidita Kemala (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The goal of education is to actively develop students' potential by establishing a learning environment and process. Most students still find learning chemistry in high school or trade school to be challenging. One way for universities to help schools grow and enhance secondary school students' skills is through the Assisted School Program. Students in this program receive training to help them develop a broad perspective, expose them to the working world, and encourage their innovative spirit. Students at the target school responded favorably to this exercise, as evidenced by the average proportion of their responses on the indicators of interest, responsiveness, and satisfaction that met positive criteria. Students at this aided school, SMK Negeri 2 Pekanbaru, responded actively to the activities 94% of the time, whereas SMK Negeri 1 Tualang received the fewest replies (72%). In general, student responses regarding their level of enthusiasm in the targeted school activities are excellent. Overall, the guided inquiry method's student replies were rated as good. This is demonstrated by the percentage of each statement falling into the very good category, the overall student response rate of 81.88%, and the pre-test and post-test results, which showed that it had an impact on students' knowledge growth as indicated by the higher post-test scores compared to the pre-test score.